Metal-induced oxidative stress activates different lipid signaling pathways in dopaminergic neurons - Sánchez Campos, Sofía (2012)
The characterization of the mechanisms mediating the effects of metal-induced oxidative stress on neuronal dysfunction and death is central in the understanding of the pathology of several neurodegenerative disorders such as Parkinson’s disease. In this work, we characterized the cellular responses that operate in dopaminergic neurons (N27 cells) exposed to an overload of transition metals such as iron (Fe, 1 mM), copper (Cu, 10 and 50 µM) or their combination for 24 hs. Under these experimental conditions, reactive oxygen species measured by fluorescence microscopy, and lipid peroxidation levels increased as a function of metal concentration. Maximum levels of lipid peroxides were observed in the presence of Fe + Cu. Cell viability, determined by MTT reduction, strongly decreased in the presence of Cu and with the combination of both metals. Under these experimental conditions, an increase in the levels of Akt phosphorylation in Ser473 was observed. Bcl-2 expression showed the same profile that Akt phosphorylation. In addition, the expression and the activation of the secretory and cytosolic isoforms of phospholipase A2 (PLA2) were differentially affected by metal overload. Our results demonstrate that phospholipid deacylation processes catalyzed by PLA2s and PI3K activation are involved in the response of dopaminergic neurons to metal-induced oxidative stress.